Dyslipidemia in Patients With Active Rheumatic Disease - Vaidya, Binit; Bhochhibhoya, Manisha (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Rheumatic diseases have been found to be associated with an increased risk of cardiovascular disease (CVD) and dyslipidemia. Constant state of inflammation among patients with active rheumatic diseases predispose to endothelial damage leading to increased risk of dyslipidemia and CVD. Dyslipidemias are being increasingly recognized as an important contributory factor towards the development of CVD and also the leading cause of death in various autoimmune diseases. We aim to study the prevalence and pattern of dyslipidemia in these patients. MATERIALS & METHODS: Consecutive patients with active rheumatic disease of >3months duration and fibromyalgia attending rheumatology OPD were included from January 2013 to January 2014. Patients with diabetes, hypertension, hypothyroidism, CAD, CKD and those on statin or fibrates were excluded. Activity was determined by clinical features, ESR and CRP levels. Data were collected on predesigned excel sheet including fasting lipid profile. RESULTS: A total of 560 patients were enrolled (RA-255, SLE-70, other-45, FMS-190). Any form of dyslipidemia was found in 75.9% of patients. Isolated raised triglyceride >300mg/dl was seen in 178 (41.9%) of them, whereas LDL>120mg/dl was seen 235(55.3%) of patients (23.7% had LDL>200). Almost all patients (98.7%) had LDL:HDL ratio of >2.5. Dyslipidemia was seen in 86 (45.2%) patients with fibromyalgia but none of them had LDL>120 mg/dl. CONCLUSION: Patients with active rheumatic disease are likely to have significant dyslipidemia which can contribute to excess cardiovascular mortality in these patients. Early identification and correction of significant lipid abnormalities may help to reduce the morbidity and mortality in these patients. Journal of Universal College of Medical Sciences (2016) Vol.04 No.01 Issue 13, page: 6-9